Do litter manipulations affect leaf functional traits of savanna woody plants? - Scalon, Marina C.; Rossatto, Davi R. [UNESP]; Franco, Augusto C. (Springer, 2014)
Plant litter is the layer composed of dead plant material that covers soil surfaces in terrestrial ecosystems. It is an important pool of essential nutrients for soil and plants, serving also as a protective layer on the soil surface. In this study, we investigated the effects of litter addition and removal on leaf functional traits of woody Neotropical savanna trees. We measured maximum photosynthesis (A (max)), stomatal conductance (g (s)), leaf transpiration (E), intrinsic water use efficiency (IWUE), specific leaf area (SLA), and chlorophyll content (CCI) in 15 species belonging to three different phenological groups (evergreen, briefly deciduous, and deciduous species) that were subjected to three distinct litter availability treatments (addition, removal, and control plots) in a Neotropical Savanna site in Brazil. Although SLA and CCI differed among phenology groups, they were not affected by the litter treatments. In contrast, when considered at the community level, we found that the availability of litter affected the leaf traits linked with the water status of the plants (E, g (s) and IWUE). Plants in the litter removal plots exhibited lower g (s) and E (25 % of reduction in comparison with control group) but higher IWUE, while plants in the litter addition plots had a 10 % decrease in IWUE but a 12 % increase in g (s) and E compared with plants in control plots. Savanna woody plants responded promptly to litter manipulation by adjusting leaf water loss, which suggests that in the short term, changes in the amount of litter in Cerrado ecosystems can affect the soil water availability to the plant community.
Keywords: Litter; Savanna; Leaf functional traits; Cerrado; Water use efficiency